Meta Analysis Study of Interpersonal Communication and Speech Delay in Early Childhood: Meta Analysis Study of Interpersonal Communication and Speech Delay in Early Childhood - Devina Junita Sujaya; Ananta Yudiarso (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Speech delay in children is closely related to their interpersonal communication. Previous studies have found that 10-20 percent of young children experience speech delay which ultimately affects their interpersonal communication. The purpose of this study was to examine the effect size of the different test and the correlation of the results of the study which linked children's interpersonal communication and speech delay. This meta-analysis uses 14 research journals. There are 11 journals using the correlation method and 3 journals using the different test method. Data were analyzed using effect size correlation and effect size difference tests. The results showed that interpersonal communication has a large correlation size effect on speech delay with r = 0.504. The different test has a small effect size, g = 0.329. The results of the correlation effect size and the different test effect size are formed by external factors related to stimulation and family support, as well as a positive environment.